Reactivity of Isocyanate-Functionalized Lignins: A Key Factor for the Preparation of Lignin-Based Polyurethanes - Zieglowski, Mareike; Trosien, Simon; Rohrer, Jochen; Mehlhase, Sabrina; Weber, Simone; Bartels, Kerstin; Siegert, Gregor; Trellenkamp, Taina; Albe, Karsten; Biesalski, Markus (Frontiers in Chemistry, 2019)
Using isocyanate-functionalized Kraft lignin as a reactive macromonomer for the preparation of polyurethane foams by a prepolymer technique is a well-known strategy to incorporate the biomacromolecule into a higher value polymer material. However, as of today the mechanical properties of the resulting materials are still insufficient for a number of possible applications. One reason for this limitation is that the reaction pathway and the morphological arrangement of such foams is of uttermost complexity and depends on a large number of influencing material-intrinsic factors. One important parameter is the reactivity of the functionalized lignin, which has a great impact on the interphase reaction kinetics and thus, on the geometry and mechanical properties of the resulting polyurethane foams. The reactivity is implied, amongst others, by the electron affinity of the isocyanate moiety. Herein, we investigate the reactivity of Kraft lignin modified with different commercially used isocyanates in the reaction with conventional polyols. Therefore, differently reactive prepolymers were synthesized, characterized and polyurethane foams were prepared thereof by using these compounds and the foam formation kinetics, morphological as well as mechanical properties were investigated. Finally, the results were supported by quantum mechanical calculations of the electron affinities of representative model compounds for the lignin-based prepolymers. This work gives rise to a better understanding of the effect of the reactivity and isocyanate structure linked to Kraft lignin on the polyurethane formation and enables rational choice of the isocyanate for pre-functionalization of lignin to prepare materials with better mechanical performance.